Odpowiedzi

Najlepsza Odpowiedź!
2010-01-02T00:40:38+01:00
Cos²α+sin²α=1
tgα*ctgα=1
sinα/cosα=tgα
cosα/sinα=ctgα
1.
(cos α/sinα + tgα) × sin²α = tgα
L=(cos α/sinα + tgα) × sin²α=(cos α/sin α+ sin α/cos α)× sin²α=
((cos²α+sin²α)/(sinα*cosα))*sin²α= (1*sin²α)/(sinα*cosα)=
sinα/cosα=tgα=P
2.
((1+(cosα/sinα)²)/1+tg²α ) × tg²α = 1
L=((1+(cosα/sinα)²)/1+tg²α ) × tg²α=
=((1+ctg²α)/(1+tg²α))*tg²α=
=(tg²α+ctg²α*tg²α)/((1+tg²α)=
=(tg²α+1)/(1+tg²α)=1=P
2010-01-02T01:59:47+01:00
1. (cos α/sinα + tgα) × sin²α = tgα


Korzystam ze wzorów:

cosα/sinα=ctgα
sinα/cosα=tgα
tgα*ctgα=1
cos²α+sin²α=1 ( jedynka trygonometryczna
L=(cos α/sinα + tgα)*sin²α
L =(cos α/sin α+ sin α/cos α)* sin²α
wspólny mianownik to : sinα*cosα
L =[(cos²α+sin²α):(sinα*cosα)]*sin²α
L = (1*sin²α) :(sinα*cosα)
redukuje się sinα w liczniku i mianowniku
L =sinα:cosα
L =tgα
P =tgα
L = P jest to tożsamość


2. ((1+(cosα/sinα)²)/(1+tg²α ) × tg²α = 1
L=[(1+(cosα/sinα)²]:(1+tg²α ) × tg²α
L =[(1+ctg²α): (1+tg²α)]*tg²α
L = tg²α(1+ctg²α) : (1+tg²α)
L =(tg²α + tg²α*ctg²α) : (1+tg²α)
L =(tg²α + 1) : (1 + tg²α)
L =(tg²α + 1) : (tg²α +1 )
L = 1
P = 1
L = P jest to tożsamość